Of an alien homecoming : reading Heidegger's Hölderlin. - CHARLES BAMBACH (STATE UNIV OF NEW YORK PR, 2022)
Few themes resonate as powerfully in Heidegger as those connected to homecoming, homeland, and Heimat. This emphasis plays out most powerfully in Heidegger's reading of Hölderlin and his turn towards language, art, and poetizing as a way of thinking through the poet's relevance in the epoch of homelessness and the abandonment of the gods. As the first book-length study in English of the Heidegger-Hölderlin relation, Of an Alien Homecoming addresses the tension within Heidegger's work between his disastrous political commitments during the era of National Socialism and his attempts to open a path to a German future nurtured on Hölderlin's ideal of poetic dwelling. Charles Bambach reads this work on Hölderlin from 1934-1948 in conversation with the Black Notebooks and Heidegger's metapolitics, even as he uncovers an ethical dimension within Heidegger that pervades his reading of poetry. Throughout all of these various stages on Heidegger's thought path, Hölderlin remains the poet who poetizes the possibility of finding our lost home amidst the homelessness brought about in the epoch of technological thinking.